Longitudinal Data to Assess Relationships among Plasma Folate, Vitamin B12, Non-esterified Fatty Acid, and β-Hydroxybutyrate Concentrations of Holstein Cows during the Transition Period - Mélissa Duplessis; Younes Chorfi; Christiane L. Girard (Metabolites, 2023)
It is well established that the plasma metabolite profile changes during metabolic dysfunction, such as elevated non-esterified fatty acid (NEFA) release when body reserve mobilization is excessive in early lactation cows. Relationships between changes in plasma concentrations of metabolites caused by a metabolic impairment and the status of vitamins, such as folates and vitamin B12, have barely been studied in cattle. This study was undertaken to assess relationships between peripartum plasma concentrations of folates, vitamin B12, NEFA, and beta-hydroxybutyrate (BHB). Longitudinal data of 48 multiparous Holstein cows from 5 studies were taken from days −14 to 21 relative to calving. Blood samples were taken weekly before calving and either twice or thrice per week postpartum, and plasma was analyzed for folate, vitamin B12, NEFA, and BHB concentrations. Postpartum plasma NEFA and BHB concentrations were negatively related to plasma folate concentration at days −14 and −7 relative to parturition, whereas the opposite relationship was noted for the plasma vitamin B12:folate ratio. The plasma folate and NEFA areas under the curve from the whole studied period were negatively associated, and the opposite was observed with the association between the plasma vitamin B12:folate ratio and NEFA as well as the BHB areas under the curve. The results suggest that there is an increased use of folate for metabolic functions during elevated concentrations of plasma NEFA and BHB. Future research should focus on finding an optimal plasma vitamin B12:folate ratio to favor cow health during the challenging period of parturition.